PRICE SUSTAINABILITY OF AGRARIAN SECTOR IN BULGARIA - M. Petrov (Trakia Journal of Sciences)
Recent years were marked by several crises of different characteristics: epidemics, energy sources, and crises in raw materials. We are witnessing how these turbulences transfer to the means of production of agricultural companies and subsequent transfer to the prices of food for people and animals. The main AIM of this study is to determine the inflation force that is hitting agricultural companies and to study their capability of sustaining their production levels. The pressure on prices in the agrarian sector originated not only from the inflation in the Bulgarian economy but also due to the turbulences in international food markets and political instability in the European continent. The METHOD of the study is a systematic analysis of statistical data regarding the agrarian production and prices of agrarian products in the markets of Bulgaria. RESULTS of the study show that there are several factors that are pressing the prices of agrarian products, pushing inflation at higher levels. Agrarian producers have a low capability to sustain their production levels and are forced to reduce or change the type of their production.